Assessment of the relationship between generalized convulsive epilepsy and systemic inflammatory regulators: a bidirectional Mendelian randomization study - Wang, Shengnan; Su, Tengfei; Pang, Shuyan; Wang, Jianglong; Lang, Yue; Zhu, Mingqin; Cui, Li (Frontiers in Neurology, 2023)
Background： Known as an important subtype of epilepsy, a syndrome of neuronal dysfunction, generalized convulsive epilepsy (GCE) is characterized by diffuse abnormal discharges of neurons within the brain. Compounding evidence suggests a correlation between epilepsy and inflammatory factors, for instance, cyclooxygenase-2, interleukin-1β, and interleukin-6. Elevated inflammatory factors have been found in patients with epilepsy and in many animal models. Therefore, inflammation may be closely related to the pathogenesis and progression of GCE. However, the cause-and-effect relationship between the two is difficult to determine due to small sample size and confounding factors. Methods: In order to test if there is a causality of 41 cytokines on GCE, we conducted a two-sample Mendelian randomization (MR) based on the largest and latest genome-wide association study (GWAS) involving 290 cases and 453,521 European controls and a GWAS meta-analysis consisting of 41 cytokines from 8,293 individuals. Results: A bidirectional causal link between cytokines and GCE is confirmed by MR.Genetically predicted increased levels of hepatocyte growth factor and decreased levels of eotaxin and interleukin-18 are associated with an increased risk of GCE (OR= 1.904, 95%CI=1.019-3.561, p=0.044; OR=0.641, 95%CI=0.417-0.984, p=0.042; OR=0.482, 95%CI=0.251-0.927, p=0.046). Furthermore, the presence of GCE is related to an increase levels of multiple cytokines, such as Macrophage inflammatory protein-1α, Interleukin-12p70, Interleukin-17, Interleukin-1 receptor antagonist and basic fibroblast growth factor (OR=1.038, 95%CI=1.005-1.073, p=0.024; OR=1.031, 95%CI=1.009-1.054, p=0.006; OR=1.027, 95%CI=1.002-1.053, p=0.037; OR=1.037, 95%CI=1.003-1.072, p=0.032; OR=1.032, 95%CI=1.000-1.066, p=0.048; OR=1.025, 95%CI=1.003-1.048, p=0026). Significance: There is a bidirectional causal link between inflammation and GCE. The detection of significantly altered factor levels may be of great significance for screening GCE and predicting the occurrence of GCE. Moreover, the available pharmacological treatments for GCE focus primarily on seizure suppression. In the future altering the concentration of these cytokines in the body through targeted anti-inflammatory therapy to modify the epileptogenesis mechanism and prevent recurrence and refractoriness of GCE, may become the key to new treatments.